1990
DOI: 10.1093/ejo/12.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maxillary protraction determined by laser metrology

Abstract: In this work we studied some of the main effects of the maxillary protraction orthopedic device. The initial dento-craniofacial reactions induced by maxillary protraction similar to that commonly employed in clinical practice are reported. The fringe counting holographic interferometry technique is used to measure displacements. The experiments were performed on a dried human skull; traction application points were situated over the permanent lateral incisors or over the first permanent molars. The results fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…For minimal rotation of the maxilla during protraction, when the force is applied inferior to the occlusal plane, the effective point of force application has been reported to be at the lateral incisors ( Canut and Dalmases, 1990 ), the canines ( Nakano and Miura, 1980 ;Ngan et al , 1997 ), the fi rst premolar ( Proffi t, 1992 ;Ko and Kim, 1995 ), and the fi rst molars ( Tanne et al , 1989 ). In clinical research using cephalometric analysis, the displacement of ANS and point A in the group protracted with a separated midpalatal suture was found to be larger than in the group where a labiolingual appliance and protraction device was used ( Baik, 1995 ;Ngan et al , 1997 ;Baccetti et al , 1998 ;Filho et al , 1998 ;Saadia and Torres, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…For minimal rotation of the maxilla during protraction, when the force is applied inferior to the occlusal plane, the effective point of force application has been reported to be at the lateral incisors ( Canut and Dalmases, 1990 ), the canines ( Nakano and Miura, 1980 ;Ngan et al , 1997 ), the fi rst premolar ( Proffi t, 1992 ;Ko and Kim, 1995 ), and the fi rst molars ( Tanne et al , 1989 ). In clinical research using cephalometric analysis, the displacement of ANS and point A in the group protracted with a separated midpalatal suture was found to be larger than in the group where a labiolingual appliance and protraction device was used ( Baik, 1995 ;Ngan et al , 1997 ;Baccetti et al , 1998 ;Filho et al , 1998 ;Saadia and Torres, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such research has also been coupled with cephalometric studies using metallic implants as radiographic reference markers to measure the relative displacement of the craniofacial bones and the effect of mechanical forces on craniofacial growth. In vitro studies have been conducted employing photoelastic (6, 7), strain gauge (8–11) and holographic (11, 12) techniques to characterize the mechanical behaviour of the craniofacial complex in response to the applied force system. Nevertheless, most of these techniques are limited in their ability to determine the actual sites of skeletal changes in a complicated structure such as the craniofacial complex.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies (5)(6)(7) reflecting the effect of maxillary protraction devices support these results. Also, experimental studies (8)(9) have shown anterior displacement of the maxilla by sutural modification of the circummaxillary sutures.…”
Section: Discussionmentioning
confidence: 99%